2013
DOI: 10.1111/jdi.12118
|View full text |Cite
|
Sign up to set email alerts
|

Age‐associated changes of islet endocrine cells and the effects of body mass index in Japanese

Abstract: Aims/Introduction: Impaired growth and premature death of b-cells are implicated in the progression of islet pathology in type 2 diabetes. It remains unclear, however, how aging affects islet cells, or whether the islet change in diabetes is an augmented process of aging. We studied age-related changes of the islet structure in Japanese non-diabetic subjects and explored the underlying mechanism of the changes. Materials and Methods: A total of 115 non-diabetic autopsy cases were subjected to morphometric anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 41 publications
7
54
1
Order By: Relevance
“…The modest reduction of b-cell mass in this study (;30%) compared with those in Americans (5) (;50-60%) may be ascribed to the lack of influences of increased BMI on Vi and Vb in Japanese nondiabetic subjects (26,27). Mean BMI was 22 in Japanese lean diabetic subjects while it was 35 in Americans (5).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The modest reduction of b-cell mass in this study (;30%) compared with those in Americans (5) (;50-60%) may be ascribed to the lack of influences of increased BMI on Vi and Vb in Japanese nondiabetic subjects (26,27). Mean BMI was 22 in Japanese lean diabetic subjects while it was 35 in Americans (5).…”
Section: Discussionmentioning
confidence: 57%
“…Mean BMI was 22 in Japanese lean diabetic subjects while it was 35 in Americans (5). In contrast to the marked increase in b-cells in obese European or American nondiabetic subjects (28), compensatory hyperplasia in obese Japanese was not apparent (26,27). Such a modest reduction of b-cells may not itself account for the poor insulin secretion encountered in diabetes, underscoring the importance of b-cell dysfunction in type 2 diabetes rather than b-cell loss (2,6,29).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…As a result, unexpectedly, we were not able to find a significant increase in beta cell mass in Japanese obese individuals compared with lean subjects (Figure 6). Another Japanese study also confirmed our findings [52]. These findings are inconsistent with the findings in the Caucasian population [24,39].…”
Section: Ethnic Difference In Beta Cell Mass With Obesitysupporting
confidence: 48%
“…More recently, Mizukami et al reported that Ki67-a marker for cell proliferation-positive rate of β and non-β islet cells is prominent in childhood but significantly decreased over 20 years of age (Mizukami et al, 2014). The pattern of telomere shortening in islet cells is compatible with the results of Cnop's and Mizukami's, suggesting that rapid islet cell telomere reduction in childhood and a slow reduction in adulthood.…”
Section: Discussionmentioning
confidence: 68%